Treatment Outcomes for Patients with Multidrug-Resistant Tuberculosis in Post-Earthquake Port-au-Prince, Haiti - Charles, Macarthur (The American Society of Tropical Medicine and Hygiene, 2014)
We report outcomes and 12-month survival for the first cohort of patients to undergo multidrug-resistant tuberculosis (MDR-TB) treatment after the earthquake in Haiti. From March 3, 2010 to March 28, 2013, 110 patients initiated treatment of laboratory-confirmed MDR-TB at the Groupe Haïtien d'Etude du Sarcome de Kaposi et des Infections Opportunistes (GHESKIO) Center in Port-au-Prince, Haiti. Twenty-seven patients (25%) were human immunodeficiency virus (HIV)-positive. As of October 31, 2013, 95 (86%) patients were either cured or alive on treatment, 4 (4%) patients defaulted, and 11 (10%) patients died. Culture conversion occurred by 30 days in 14 (13%) patients, 60 days in 49 (45%) patients, and 90 days in 81 (74%) patients. The probabilities of survival to 12 months were 96% (95% confidence interval [95% CI] = 89–99) and 85% (95% CI = 64–94) for HIV-negative and -positive patients, respectively. Despite adverse conditions, outcomes for patients with MDR-TB are highly encouraging. Major efforts are underway to scale up community directly observed therapy and expand care to other regions of Haiti.